2016
DOI: 10.1515/bmt-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic effects after Diode and Er:YAG laser irradiation of grade IV and V titanium implants placed in bone – an ex vivo study. Preliminary report

Abstract: Many inserted implants are affected by peri-implantitis. The aim of our study was to evaluate increases in implant temperature, depending on the diameter and chemical composition of implants. In particular we measured the time it takes for the temperature of an implant to rise by 10°C and evaluated laser power settings required to prevent thermal injury when an implant surface is decontaminated during the treatment of peri-implantitis. The study analysed six implants placed in porcine ribs and divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 52 publications
3
43
0
1
Order By: Relevance
“…Lasery diodowe są stosowane jako narzędzia do ustawiania pozycji urzą-dzeń diagnostycznych (MRT, CT, CBCT) oraz same służą jako instrumenty diagnostyczne i terapeutyczne [4]. W stomatologii laserów diodowych używa się do: diagnostyki próchnicy, biostymulacji, fotoaktywnej dezynfekcji, cięcia i łączenia tkanek miękkich, leczenia zapalenia okołowszczepo-wego, łagodzenia bólu czy oczyszczania zakażo-nych kanałów korzeniowych [5][6][7][8][9][10][11][12].…”
unclassified
“…Lasery diodowe są stosowane jako narzędzia do ustawiania pozycji urzą-dzeń diagnostycznych (MRT, CT, CBCT) oraz same służą jako instrumenty diagnostyczne i terapeutyczne [4]. W stomatologii laserów diodowych używa się do: diagnostyki próchnicy, biostymulacji, fotoaktywnej dezynfekcji, cięcia i łączenia tkanek miękkich, leczenia zapalenia okołowszczepo-wego, łagodzenia bólu czy oczyszczania zakażo-nych kanałów korzeniowych [5][6][7][8][9][10][11][12].…”
unclassified
“…Nonetheless, the impact of blue lasers on implant temperature has already been analyzed in relation to laser power. 13,[19][20][21][22] The main objective of this study was to determine effective and safe energy settings for a 445 nm diode laser operating in contact and non-contact mode for implants made from pure titanium (grade IV) in comparison with an infrared wavelength of 980 nm.…”
Section: Discussionmentioning
confidence: 99%
“…12 Some studies have shown that the Er:YAG laser induced minimal peri-implant temperature increase, has the positive effects for pain decrease and facilitates a prosthetic impression procedure. 13,14 Other studies using a CO 2 laser proved its disadvantage: an increase in the titanium implant temperature. There is only one study in the literature, conducted by Fornaini et al, regarding the surgical use of the KTP laser for implant second stage surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Laser intervention significantly reduces postoperative pain, discomfort and swelling, and causes only a minimal thermal rise in the bone around the implant. [24][25][26] The ab- …”
Section: Discussionmentioning
confidence: 99%